solid geometry
in Calculus Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

f(g(x))=3g(x)+2=3(2x+A)+2=6x+3A+2;

g(f(x))=2f(x)+A=2(3x+2)+A=6x+4+A.

Therefore since f(g(x))=g(f(x)), 3A+2=4+A, 2A=2, A=1.

by Top Rated User (738k points)

Related questions

1 answer
asked Mar 1, 2017 in Calculus Answers by lovelymath Level 2 User (1.9k points) | 463 views
1 answer
1 answer
1 answer
asked Mar 1, 2017 in Calculus Answers by lovelymath Level 2 User (1.9k points) | 616 views
1 answer
asked Sep 22, 2014 in Algebra 2 Answers by jackie | 142 views
1 answer
asked Sep 22, 2014 in Algebra 2 Answers by jackie | 154 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,775 questions
89,828 answers
2,031 comments
30,046 users